Prebiotic potential of enzymatically produced ulvan oligosaccharides using ulvan lyase of Bacillus subtilis, NIOA181, a macroalgae‐associated bacteria - Jagtap, Ashok S.; Parab, Ashutosh S.; Manohar, Cathrine S.; Kadam, Nitin S. (Journal of applied microbiology, 2022)
Aims To characterize the polysaccharide hydrolyzing potential of macroalgae‐associated bacteria (MABs) for the enzymatic production of oligosaccharides and determining their prebiotic potential. Methods and Results Approximately 400 MABs were qualitatively characterized for polysaccharide hydrolyzing activity. Only about 5%–15% of the isolates were found to have the potential for producing porphyranase, alginate lyase and ulvan lyase enzymes, which were quantified in specific substrate broths. One potential MAB, Bacillus subtilis, NIOA181, isolated from green macroalgae, showed the highest ulvan lyase activity. This enzyme was partially purified and used to hydrolyse ulvan into ulvan oligosaccharides. Structural characterization of ulvan oligosaccharides showed that they are predominantly composed of di‐, tri‐ and tetrasaccharide units. Results showed that the enzymatically produced ulvan oligosaccharides exhibited prebiotic activity by promoting the growth of probiotic bacteria and suppressing the enteric pathogens, which were higher than the ulvan polysaccharide and equivalent to commercial fructooligosaccharides. Conclusions A potential MAB, NIOA181, producing ulvan lyase was isolated and used for the production of ulvan oligosaccharides with prebiotic activity. Significance and Impact of the Study Rarely studied ulvan oligosaccharides with prebiotic activity can be widely used as an active pharmaceutical ingredient in nutraceutical and other healthcare applications.